Estimating the recreation value of ecosystems by using a travel cost method approach - Mendes, Isabel (2010)
Recreation is one of the ecosystem's secondary values of a well conserved natural ecosystem, associated with the direct use individuals make of these natural assets. In this paper we define and estimate the total economic recreation value to visitors of a particular natural area, a national park. An on-site individual observation Travel Cost Model, Count Data distributions, and a version of hyperbolic discounting framework distribution were used to estimate a measure for the present recreation use of the site and the total discounted recreation value for a 50 years period. The empirical estimates of the average representative visitor's present equivalent surplus willingness to pay, based on the impact assumption of closure or loss of access to the park were 123 € per day per visit, and 593 € per each average five days length visit, per visitor. These values suggest that recreation use of nature has a higher value than certain economic activities in the area.